Phosphoribosylformylglycinamidine Synthase (PFAS) Deficiency: Clinical, Genetic and Metabolic Characterisation of a Novel Defect in Purine de Novo Synthesis - Zikanova, Marie; Skopova, Vaclava; Stuurman, Kyra E; Baresova, Veronika; Souckova, Olga; Hnizda, Ales; Krijt, Matyas; Bleyer, Anthony J; Zeman, Jiri; Kmoch, Stanislav (Journal of inherited metabolic disease, 2025)
Purine de novo purine synthesis involves 10 reactions catalysed by six enzymes, including phosphoribosylformyglycinamidine synthase (PFAS). To date, genetic defects of three of these enzymes, namely ATIC, ADSL and PAICS, have been characterised in humans. Here, we report for the first time two individuals with PFAS deficiency. Probands were identified through metabolic and genetic screening of neurologically impaired individuals. The pathogenicity of the variants was established by structural and functional studies. Probands C1 and C2 presented with prematurity, short stature, recurrent seizures and mild neurological impairment. C1 had elevated urinary levels of formylglycineamide riboside (FGAr) and bi-allelic PFAS variants encoding the NP_036525.1:p.Arg811Trp substitution and the NP_036525.1:p.Glu228_Ser230 in-frame deletion. C2 is a 20-year-old female with a homozygous NP_036525.1:p.Asn264Lys substitution. These amino acid changes are predicted to affect the structural stability of PFAS. Accordingly, C1 skin fibroblasts showed decreased PFAS content and activity, with impaired purinosome formation that was restored by transfection with pTagBFP_PFAS_wt. The enzymatic activities of the corresponding recombinant mutant PFAS proteins were also reduced, and none of them, after transfection, corrected the elevated FGAR/r levels in PFAS-deficient HeLa cells. While genetic defects in purine de novo synthesis are typically considered in patients with severe neurological impairment, these disorders, especially PFAS deficiency, should also be considered in milder phenotypes.
Keywords: mutace; Female; předškolní dítě; mladý dospělý; ženské pohlaví; Carbon-Nitrogen Ligases with Glutamine as Amide-N-Donor; formylglycinamide riboside; purine de novo synthesis; FGAR; puriny; metabolic disorder; Purine-Pyrimidine Metabolism, Inborn Errors; lidé; PFAS deficiency; Mutation; poruchy metabolismu purinů a pyrimidinů; purinosome; Male; Child, Preschool; Young Adult; Purines; ligasy tvořící vazby C-N s glutaminem jako amidovým donorem; mužské pohlaví; Humans